P-153 Stopping traffic. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Ward, Beth
Abstract : Demelza Hospice Care for Children, Sittingbourne, Kent, UK The United Kingdom is one of the most prominent destination countries for people to be trafficked to in Europe. An estimated 20 000 people are trafficked into (and throughout) the UK every year, with the majority of victims coming from, arguably, the poorest countries. This presentation outlines the case of a baby (aged two days) who was referred to a children's hospice for end of life care. Within the context of the direct work, it became apparent that the mother had been trafficked into the UK and had experienced periods of homelessness. The children's hospice social work team worked intensively to seek support for this mother, but due to high service demand, and the mother's questionable residency status, no statutory organisation was willing to engage. The NSPCC helpline recommended the Salvation Army, a Christian church and registered charity and this partner charity offered an assessment visit by their Anti-Human Trafficking Team's First Responder Co-ordinator and plans were subsequently put in place for the team to take on the supporting role after the baby's death. As well as focusing on safeguarding this extremely vulnerable family unit, it was essential that this mother had the opportunity to bond with her baby and to, albeit briefly, positively experience motherhood. The baby died peacefully, aged seven weeks. Pre-death planning had clarified the family's customs and rituals, which dictated that the parents did not attend the funeral and therefore, two members of the children's hospice team, together with two representatives from the Salvation Army were present, as a mark of respect. A year on, the mother continues to receive concerted support from the partnership charity, enabling her to preserve her dignity, reflect, recover and rebuild her life.